A Dense Plasma Globule in the Solar Neighborhood - Vedantham, H.; Bruyn, A.; Macquart, Jean-Pierre (Institute of Physics Publishing, 2017)
© 2017. The American Astronomical Society. All rights reserved. The radio source J1819+3845 underwent a period of extreme interstellar scintillation between circa 1999 and 2007. The plasma structure responsible for this scintillation was determined to be just 1-3 pc from the solar system and to posses a density of n e ~ 10 2 cm -3 , which is three orders of magnitude higher than the ambient interstellar density. Here we present radio-polarimetric images of the field toward J1819+3845 at wavelengths of 0.2, 0.92, and 2 m. We detect an elliptical plasma globule of approximate size 1° × ?2° (major-axis position angle of ˜-40°), via its Faraday-rotation imprint (˜15 rad m -2 ) on the diffuse Galactic synchrotron emission. The extreme scintillation of J1819+3845 was most likely caused at the turbulent boundary of the globule (J1819+3845 is currently occulted by the globule). The origin and precise nature of the globule remain unknown. Our observations represent the first time that plasma structures which likely cause extreme scintillation have been directly imaged.